HMAS Bataan, 1952 : an Australian warship in the Korean War - Cooper, Anthony James, 1961- (University of New South Wales Press, 2010)
A unique account of Australia's involvement in the Korean War, this record tells the story of destroyer HMAS Bataan's 1952 tour of duty. Written from two contrasting perspectives, namely from a lower deck seaman and an upper deck commander, this narrative draws on a variety of archival sources, including the ship's monthly log, a collection of poetry written aboard the ship during the war, letters, and photographs. Peppered with intimate insights from the unpublished notebooks, this chronicle will entice those interested in naval and military history.